Draft Annual Plan 1978-79 Sikkim State - Planning Commission (Planning Commission, 1997)
The Graft Annual Plan for 1978-79 envisages an investment of Rs. 16.60 crores in the State sector. the outlay represents a step up of about 33% from the current year’s State sector investment of F.s. 12.47 crores. the enhancement in the outlay has become necessary in view of the tempo in economic development generated as a consequence of investment in the first two years of the Fifth Plan. the three-year outlay from 1976 to 1979, which was finalised by the National Development Council proposed an investment of 39.64 crores.
Government of Sikkim Planning and Development Department